Meaningful work as realization and justification: Toward a dual conceptualization. (May 2017) - Lepisto, Douglas A.; Pratt, Michael G.
We review and develop two alternative conceptualizations of meaningful work: a predominant perspective we label realization and an underdeveloped, yet critical, perspective we label justification. We develop each conceptualization by identifying the core problem meaningful work is thought to address and accompanying solutions. Next, we build from this distinction to propose a research agenda that advances scholarly understanding of meaningful work from a justification perspective. Through building this research agenda, we elevate scholarly understanding on meaningful work by illuminating new foci for research, highlighting the relevance of social-cultural mechanisms, and suggesting alternative outcomes.